2022
DOI: 10.1177/13506501221129091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Elastic-Plastic Loading and Unloading Contact between Ellipsoid and Rigid Flat

Abstract: The loading contact behaviour of ellipsoids has been extensively studied, although there is limited research on their loading and unloading contact behaviour. This study uses the finite element method to analyse loading and unloading contact between an elastic-plastic ellipsoid and a rigid body. Unloading of an ellipsoid with different ellipticities was precisely conducted at the end of the elastic-plastic state. The ellipticity of the contact area is related to interference during loading and is independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Although most studies adopt a spherical shape to represent asperities, implying a circular contact area, research such as those by Nayak (1971) and Bush, Gibson & Thomas (1975), demonstrated that asperities tend to resemble more an ellipsoidal or elliptical paraboloid shape, resulting in elliptical contact areas. As mentioned by Zhang et al (2023), the ellipsoidal representation of an asperity is more appropriate due to variations in curvature radii in different directions, resulting from the relative motion of cutting tools during surface manufacturing processes.…”
Section: Geometric Characterization Of Asperitiesmentioning
confidence: 99%
“…Although most studies adopt a spherical shape to represent asperities, implying a circular contact area, research such as those by Nayak (1971) and Bush, Gibson & Thomas (1975), demonstrated that asperities tend to resemble more an ellipsoidal or elliptical paraboloid shape, resulting in elliptical contact areas. As mentioned by Zhang et al (2023), the ellipsoidal representation of an asperity is more appropriate due to variations in curvature radii in different directions, resulting from the relative motion of cutting tools during surface manufacturing processes.…”
Section: Geometric Characterization Of Asperitiesmentioning
confidence: 99%